Collective reflexivity in social marketing through ethnographic film-making: The Yolngu story of tobacco in Yirrkala, Australia. (March 2020) - Kariippanon, Kishan; Gordon, Ross; Jayasinghe, Laknath; Gurruwiwi, Glen
This article aims to extend the concept of collective reflexivity into marketing theory. We also identify the potential of ethnographic film-making as an approach for fostering collective reflexivity in social marketing. We focus on the making of an ethnographic film called Ngarali: The Tobacco Story of Arnhem Land, arguing that collective reflexivity is an important theoretical concept and practical objective in social marketing that can help address issues around creating social ties and social identity and of sharing metaphoric meaning. Conceptually, we argue that collective reflexivity encourages us to rethink reflexivity in social marketing and consumer research through a relational perspective. Furthermore, we extend current conceptualisations of collective reflexivity by identifying how sharing metaphoric meaning can act as a vehicle for its occurrence. We argue that facilitating collective reflexivity through ethnographic film-making can offer a more culturally respectful approach to social marketing.